Effect of slow breathing training on heart rate, spontaneous respiratory rate and pattern of breathing - Adhana, Ritu; Agarwal, Moneet; Gupta, Rani; Dvivedi, Jyoti (International Journal of Research in Medical Sciences, 2016)
Background: The study was performed to see the effect of slow breathing (6 breaths/minute) training on spontaneous respiratory rate, heart rate and pattern of breathing. Methods: Sixty subjects between the ages 20-50 years were included in the study. After the rest of 10 -15 minutes in a comfortable sitting posture their baseline heart rate (HR), respiratory rate (RR) and pattern of breathing were recorded on digital polygraph. Then they were guided to do slow breathing maintaining rate of around 6 per minute. Subjects were then instructed to do slow breathing exercise for 8-10 minutes twice daily for next three months. Subjects reported back after three months of practicing slow breathing and their HR, RR, and pattern of breathing were again assessed by digital polygraph. Results: After three months of practicing slow breathing there was statistically significant reduction in heart rate and spontaneous respiratory rate. Shifting of pattern of breathing from thoracic pattern to abdominal pattern of breathing was also very highly significant. Conclusions: The study showed that slow breathing technique causes comprehensive change in body physiology by controlling autonomic nervous system. It regularizes rate and pattern of breathing.